2002
DOI: 10.1097/00004872-200202000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Intima–media thickness: a new tool for diagnosis and treatment of cardiovascular risk

Abstract: Increased intima-media thickness (IMT) is a non-invasive marker of early arterial wall alteration, which is easily assessed in the carotid artery by B-mode ultrasound, and more and more widely used in clinical research. Methods of IMT measurement can be categorized by two approaches: (i) measurement at multiple extracranial carotid sites in near and far walls and (ii) computerized measurement restricted to the far wall of the distal common carotid artery. Because IMT reflects global cardiovascular risk, its no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
369
4
31

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 536 publications
(414 citation statements)
references
References 107 publications
10
369
4
31
Order By: Relevance
“…In several observational and clinical studies, except one which demonstrated a weak correlation, the IMT has been a marker of subclinical vascular cardiac disease, in association with traditional risk factors for coronary heart disease (according to our findings: CRP, LDL-cholesterol and DBP) and the coronary atheroma load, being a predictor of subsequent cardiovascular events and an early indicator of atherosclerosis, besides being a valuable risk marker in noninvasive assessments [5][6][7][10][11]14,[20][21][22][23][24][25][26][27] . With regard to carotid structural properties, no comparison with previous studies with the same group profiles could be conducted because none was found in the medical literature.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In several observational and clinical studies, except one which demonstrated a weak correlation, the IMT has been a marker of subclinical vascular cardiac disease, in association with traditional risk factors for coronary heart disease (according to our findings: CRP, LDL-cholesterol and DBP) and the coronary atheroma load, being a predictor of subsequent cardiovascular events and an early indicator of atherosclerosis, besides being a valuable risk marker in noninvasive assessments [5][6][7][10][11]14,[20][21][22][23][24][25][26][27] . With regard to carotid structural properties, no comparison with previous studies with the same group profiles could be conducted because none was found in the medical literature.…”
Section: Discussionsupporting
confidence: 55%
“…The presence of atherosclerosis is pronounced even before the clinical event, and much research has been conducted on early detection of atherosclerosis, both in DM2 and non-DM2 patients, over the last two decades 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIMT plays a role in predicting the risk of cardiovascular diseases and in turn provides information on relevant therapeutic strategies, making it a surrogate marker or an intermediate end point for observational studies and interventional therapy. 2,[4][5][6][7] Although it is clear that CIMT is a good predictor of subsequent cardiovascular diseases, it is important to establish whether the incremental information obtained by carotid ultrasound further defines an individual's risk profile, which is still in controversy 8 and data to indicate that measurement of CIMT may be useful in symptomatic patients to further distinguish patients into higher-risk or lower-risk group are presently not available. 5 Since measurement of arterial wall IMT made with B-ultrasound used in 1986, great developments had been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of a standardized method of measuring CIMT is critical for further utilization and in urgent need. 4,8 The purpose of this study is to investigate the relationships between cardiovascular events (MI, stroke and peripheral arterial disease (PAD)) and CIMT in middle-aged and older adults in Beijing, China; to assess which of the indexes, IMT in the CCA, internal carotid artery (ICA) and carotid bifurcation (CB) separately or in combination, is a better correlate.…”
Section: Introductionmentioning
confidence: 99%